Restrição de capital e as operações de cessão de crédito: um estudo com bancos brasileiros - Ribeiro, Fernanda Vieira Fernandes (2012)
The main objective of this dissertation is to investigate if there is positive relationship between capital constrained and loan sales made by Brazilian banks. The period of analysis, from June 2004 to June 2009, includes the impact of financial crisis, what is relevant due to the difficulty faced by financial institutions with the reduction in interbank lending. This study is divided into four sections, an introduction and a conclusion. In the first section is presented the literature, institutional and regulatory aspects of the loan sales in Brazilian banks. The following one develops descriptive statistics and an overview of the evolution of loan sales in Brazil. The third section presents the methodology and the model – Logit, Tobit and related models with panel data, considering the sales of total loans, with and without recourse – including a description of the variables used in each case. The results and robustness tests indicate that an increase in capital constrained is related to the expansion of loan sales by Brazilian banks. That also confirms the hypothesis that the capital constrained effects rise during periods of financial crisis.